Factors Affecting the Postoperative Bowel Function and Recurrence of Surgery for Intestinal Deep Endometriosis - Xu, Ping; Wang, Jianzhang; Zhang, Yanan; Zhu, Libo; Zhang, Xinmei (Frontiers in Surgery, 2022)
Objective: To evaluate the factors associated with complications and long-term results in surgical treatment of intestinal deep endometriosis and to figure out the optimized treatment measures for bowel endometriosis. Methods: A retrospective study was performed in a single center in China. Medical charts were reviewed from 61 women undergoing surgical treatment for bowel endometriosis between Jan 2013 and Aug 2019 in the Department of General Gynecology, Women’s Hospital School of Medicine Zhejiang University. Multivariate regression analysis was utilized to investigate the impact of the stages of endometriosis and surgical steps (independent risk factors) on complications (and postoperative bowel dysfunction). The clinical characters, surgical procedures, postoperative treatment, complications and recurrence rate were summarized and analyzed by using Lasso regression. Results: Surgery type was the most important independent risk factor related to postoperative abnormal defecation in intestinal deep endometriosis patients (P<0.05, OR=34.133). Infection is the most important independent risk factor related to both postoperative complications (OR=96.931) and recurrences after conservative surgery (OR=4.667). Surgery type and age were significantly related to recurrences after conservative surgery. Conclusions: We recommended conservative operation especially full-thickness disc excision to improve the quality of life of IDE patients. In addition, prevention of infection is very important to reduce the postoperative complications rate and the recurrence rate. Keywords: intestinal deep endometriosis, segmental resection, disc excision, shaving, postoperative bowel function, complication, recurrence.